Undercover bromance - Adams, Lyssa Kay (Adams, Lyssa Kay. Bromance book club., 2020)
"Braden Mack has read so many romance novels that he's confident he's an expert on romance and women. He is wrong. When Liv Papandreas landed a job working at the restaurant of celebrity chef Royce Preston one year ago, she knew she'd have to endure his infamous anger and abusive outbursts for the sake of her career. But when she overhears the man sexually harassing a young hostess at the restaurant, she confronts him and tells the young woman she'll escort her to human resources. To her dismay, the woman refuses to make a complaint--and the next thing Liv knows, she's out of a job. She vows that Royce Preston has not heard the last of her. But to take on the powerful chef, she knows she's going to need help. Unfortunately, the only person she can think of is Braden Mack. Mack has never met a woman he couldn't woo... except Liv. When she texts him out of the blue one day and asks to meet him for a drink that night, he thinks he might finally be getting a chance to put some of the famous Mack moves on her. Instead, she fills him in on her problem and asks for help. With the aid of the Bromance Book Club (who are inspired by the romantic suspense novel they're currently reading), they set out to take down the chef. And Liv is determined to keep the sparks between her and Mack to a minimum lest she get burned"--